2022
DOI: 10.1021/acsomega.1c07133
|View full text |Cite
|
Sign up to set email alerts
|

Mangifera indica Leaf (MIL) as a Novel Material in Atmospheric Water Collection

Abstract: Here, Mangifera indica leaves (MILs) have been used to collect atmospheric water for the first time. This novel material has been viewed by mankind as environmental waste and is mostly discarded or incinerated, causing environmental pollution. By turning waste into wealth, MILs have proven resourceful and can help ameliorate the water crisis, especially in tropical countries. The unprecedented water collection result is enough to describe MILs as an ideal material for atmospheric water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Figure bii displays a ridge valley-like surface, which aided the pinning of droplets. The detailed surface morphology of MIL is given in one of our previous papers . Under constant moisture generation conditions, the microgrooves will be filled first before extruding to connect other droplets for collection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure bii displays a ridge valley-like surface, which aided the pinning of droplets. The detailed surface morphology of MIL is given in one of our previous papers . Under constant moisture generation conditions, the microgrooves will be filled first before extruding to connect other droplets for collection.…”
Section: Resultsmentioning
confidence: 99%
“…The suction behavior of tiny droplets set the stage for a new circle, thereby impeding the formation of large droplets. In our previous work, 41 it was found that it took a total of 6.47 s for a water film to be formed on the MIL surface when compared to the BM surface with 5.90 s. Due to the natural composition of the MIL surface, a liquid bridge was achieved with the continued generation of moisture, thereby eventually covering the microgrooves for collection. Some novel and intriguing departure behaviors of droplets on the functional surfaces were observed and compared during the collection at respective orientation angles (30, 45, and 60°).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though MIL cannot be grown or found throughout the world but it can be used as a template to replicate water harvesting structures. In one of our recent works [ 28 ], we studied the wettability and droplet collection dynamics of MIL; it was understood that the combination of microgrooves, curvature, apex, and veins aided the coalescence and transportation of water droplets. The secret to such droplet movement lies in the unique structural feature of the surface as shown in Figure 1 b,c.…”
Section: Introductionmentioning
confidence: 99%